2017
DOI: 10.1002/2017tc004689
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Stacking of HP/LT Metamorphic Rocks in Accretionary Wedges and the Role of Shallowing Slab‐Mantle Decoupling

Abstract: High‐pressure/low‐temperature (HP/LT) chloritoid‐bearing micaschists crop out widely in the central part of northern Turkey and represent deep‐seated subduction‐accretionary complexes. Three peak metamorphic assemblages are identified in the area studied: (1) garnet‐chloritoid‐glaucophane with pseudomorphs after lawsonite; (2) chloritoid with pseudomorphs after glaucophane; and (3) chloritoid with pseudomorphs after jadeite in addition to phengite, paragonite, quartz, chlorite, rutile, and apatite. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 104 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…Simplified late Jurassic to Quaternary stratigraphy for the northern and southern slope of the Sinop range (with the thickness of each formation in parenthesis; Derman & İztan, ; Görür & Tüysüz, ; Hippolyte et al, , ; Ilgar, ; Janbu et al, ; Leren et al, ; Okay et al, , , ; Tüysüz et al, ). Major regional and local tectonomagmatic, metamorphic, and geodynamic events are reported with a thin black line (from: 1, Okay et al, ; 2, Aygül et al, ; 3, Meijers et al, ; 4, Aygül & Oberhansli, ; 5, Okay et al, ; 6, Kaymakçı et al, ; 7 Van Hinsbergen et al, ; 8, Özcan et al, ; 9, Dinçer, ; 10, Topuz et al, ; 11, Göçmengil et al, ; 12, Lefebvre et al, ; 13, Gürer et al, ; 14, Boztuğ & Jonckheere, ; 15, Okay et al, ; 16, Şengör et al, ), while the timing and magnitude of cooling obtained in this study is shown with a thicker black line. Gray transparent polygons show major cooling events depicted by our modeling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Simplified late Jurassic to Quaternary stratigraphy for the northern and southern slope of the Sinop range (with the thickness of each formation in parenthesis; Derman & İztan, ; Görür & Tüysüz, ; Hippolyte et al, , ; Ilgar, ; Janbu et al, ; Leren et al, ; Okay et al, , , ; Tüysüz et al, ). Major regional and local tectonomagmatic, metamorphic, and geodynamic events are reported with a thin black line (from: 1, Okay et al, ; 2, Aygül et al, ; 3, Meijers et al, ; 4, Aygül & Oberhansli, ; 5, Okay et al, ; 6, Kaymakçı et al, ; 7 Van Hinsbergen et al, ; 8, Özcan et al, ; 9, Dinçer, ; 10, Topuz et al, ; 11, Göçmengil et al, ; 12, Lefebvre et al, ; 13, Gürer et al, ; 14, Boztuğ & Jonckheere, ; 15, Okay et al, ; 16, Şengör et al, ), while the timing and magnitude of cooling obtained in this study is shown with a thicker black line. Gray transparent polygons show major cooling events depicted by our modeling.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, however, that such a collision seems to postdate the Late Cretaceous (83 to 65 Ma) oroclinal bending in the Central Pontides (Meijers et al, ). A possible explanation could be that oroclinal bending processes took place during the collision between the intraoceanic Kosdağ magmatic arc (Aygül & Oberhansli, ) and the active Southern Eurasian margin. This scenario would imply that the Paleocene collision with the Kırşehir Block did not produce significant indentation and rotations along a vertical axis as previously thought (Kaymakçı et al, ; Meijers et al, ), but rather only fault‐related exhumation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations